Learning to Write in English: EFL Students' Perceptions of Using the Wattpad as Digital Literacy in Writing Classes - Fildatul Hammi; Henny Rahmawati (IJELR: International Journal of Education, Language, and Religion, 2023)
The existence of an online reading and writing application namely Wattpad becomes a space for students to read and write which already has many users, especially students. Therefore, this study was conducted to determine students' perceptions of the use of Wattpad in the development of writing skills especially in narrative text. This research was designed by a survey and supported by semi-structured interviews of 200 English students who use Wattpad for approximately one month-six months. Then four students were interviewed which, respectively, both had positive and negative perceptions. The results were that most of the students have positive perceptions of Wattpad and had great potential in developing students' interests and writing skills. By using this application, students feel happy and enjoy exploring their writing. Therefore, Wattpad is recommended for teachers in learning because Wattpad can make independent learning for students in their writing.